Revisiting the behavior–emissions link: A multiplicative modeling approach with large-scale mobile data - Yusi Luo; Dong Zhang; Ping Huang; Yongqi Hou; Pengjun Zhao; Ling Li (Travel Behaviour and Society, 2026)

Effects of affordable housing transition on residents' activity-travel behavior in Shenzhen: Evidence from longitudinal mobile phone data - Ling Li; Ping Huang; Yusi Luo; Pengjun Zhao (Journal of Transport Geography, 2026)

A Carbon Fiber-Reinforced Backfill Composite with Self-Sensing Capability for Mine Stability Monitoring - Bozhi Zhao; Shan Ning; Jingmin Xu; Tianyu Li; Wei Luo; Pengjun Gao; Weibing Zhu (Rock Mechanics and Rock Engineering, 2025)

Impact on nonlinear runoff of LID facilities and parameter response in the TVGM model - Pengjun Li; Luwen Zhuang; Kairong Lin; Dunxian She; Qiang Wang; Wei Luo; Jianliang He; Jun Xia (Journal of Hydrology, 2025)

Experimental Study of Hot Spot Stress for Spatial CHS KK-Joints - Kang Wang; Yuhang Wang; Shan Gao; Bin Wang; Jinzhong Chen; Pengjun Luo (Journal of Marine Science and Engineering, 2023)
In offshore structures such as offshore wind turbine jacket foundations, prolonged exposure to wind and wave loads can lead to fatigue failure, especially at the joint connections. Currently, international codes primarily evaluate the fatigue performance of tubular joints using the hot spot stress (HSS) method, with stress concentration factor (SCF) being the most crucial parameter. Numerous studies have investigated the SCF of tubular joints and proposed corresponding calculation formulas. However, most of these studies have focused on simple basic loading cases. To comprehensively understand the distribution pattern of the HSS method at spatial tubular joints, this study selects the spatial CHS KK-joints as the research subject and performs the HSS testing on spatial KK-joints. The research indicates that, in CHS joints, the distribution of the HSS on the chord side remains consistent under tensile or compressive loading conditions along the brace axis. Additionally, within spatial joints, the loading conditions of neighboring braces near the reference brace significantly affect the distribution of HSS on the chord side and exhibit varying spatial effects on the SCF. Furthermore, this study applies recommended calculation formulas from codes to analyze the experimental results. The findings reveal significant discrepancies between the SCF calculation formulas recommended by CIDECT and the test results, rendering it inadequate for accurately calculating the SCF of spatial KK-joints. Therefore, further research is required to develop suitable calculation formulas for SCFs in spatial KK-joints.

An acidic β-mannanase from Penicillium sp. C6: gene cloning and over-expression in Pichia pastoris - Hongying Cai; Pengjun Shi; Huoqing Huang; Huiying Luo; Yingguo Bai; Peilong Yang; Kun Meng; Bin Yao (World Journal of Microbiology and Biotechnology, 2011)

Diversity, abundance and characterization of ruminal cysteine phytases suggest their important role in phytate degradation - Huoqing Huang; Rui Zhang; Dawei Fu; Jianjie Luo; Zhongyuan Li; Huiying Luo; Pengjun Shi; Peilong Yang; Qiyu Diao; Bin Yao (Environmental Microbiology, 2011)
Summary A novel class of cysteine phytase showing ability to degrade phytate has recently been isolated from rumen bacteria. To expand our knowledge of this enzyme class, a total of 101 distinct cysteine phytase gene fragments were identified from the ruminal genomic DNA of Bore goats and Holstein cows, and most of them shared low identities (

A novel xylanase, XynA4-2, from thermoacidophilic Alicyclobacillus sp. A4 with potential applications in the brewing industry - Jianshe Wang; Yingguo Bai; Pengjun Shi; Huiying Luo; Huoqing Huang; Jun Yin; Bin Yao (World Journal of Microbiology and Biotechnology, 2011)

A new xylanase from thermoalkaline Anoxybacillus sp. E2 with high activity and stability over a broad pH range - Jianshe Wang; Yingguo Bai; Peilong Yang; Pengjun Shi; Huiying Luo; Kun Meng; Huoqing Huang; Jun Yin; Bin Yao (World Journal of Microbiology and Biotechnology, 2010)

Characterization of a chromosomal segment showing xylanolytic activity from the symbiotic Sphingobacterium sp. TN19 - Junpei Zhou; Kun Meng; Peilong Yang; Pengjun Shi; Yaru Wang; Huiying Luo; Bin Yao (World Journal of Microbiology and Biotechnology, 2010)

Phytase production by fermentation of recombinant Pichia pastoris in monosodium glutamate wastewater - Yingguo Bai; Peilong Yang; Yaru Wang; Pengjun Shi; Huiying Luo; Kun Meng; Bo Wu; Bin Yao (World Journal of Microbiology and Biotechnology, 2009)

Gene cloning, expression and characterization of an α-galactosidase from Pedobacter nyackensis MJ11 CGMCC 2503 with potential as an aquatic feed additive - Xiaodan Liu; Kun Meng; Yaru Wang; Pengjun Shi; Tiezheng Yuan; Peilong Yang; Huiying Luo; Yingguo Bai; Bin Yao (World Journal of Microbiology and Biotechnology, 2009)

A thermophilic and acid stable family-10 xylanase from the acidophilic fungus Bispora sp. MEY-1 - Huiying Luo; Jiang Li; Jun Yang; Hui Wang; Yuhui Yang; Huoqing Huang; Pengjun Shi; Tiezheng Yuan; Yunliu Fan; Bin Yao (Extremophiles, 2009)